Intramammary coinfection by vaccinia virus and staphylococcus aureus in a bovine vaccinia outbreak - Antunes, João Marcelo Azevedo de Paula [UNESP]; Ribeiro, Márcio Garcia [UNESP]; Megid, Jane [UNESP] (SGM, 2015)
Introduction: Bovine vaccinia virus (VACV) is a well-known zoonotic agent related to exanthemous lesions in skin and mucous membranes of dairy cattle and humans, characterized by the formation of vesicles, pustules and ulcers. Mastitis is one of the most common infectious diseases of dairy herds. Bovine mammary infections are caused mainly by bacterial microorganisms, especially staphylococci. To the best of our knowledge, intramammary coinfection with VACV and Staphylococcus aureus in cows has not been reported previously. Case presentation: During an outbreak of exanthematic bovine VACV infection with animals showing vesicles, pustules and haemorrhagic ulcers on the teats, milk samples were collected for mastitis detection. Conclusion: The present report describes a case of intramammary coinfection by VACV and S. aureus in a bovine VACV outbreak.
Keywords: Bovine mastitis; Coinfection; Staphylococcus aureus; Vaccinia virus